PENGARUH KEBIJAKAN KREDIT TERHADAP MINAT PEMINJAM DI CU KELING KUMANG KELAM - Riska Witalia Rosali; Darius Damestuteles; Stefanus Masiun (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2025)
This study aims to analyze the effect of credit policies, consisting of interest rates and loan collateral, on borrowers’ interest at Credit Union (CU) Keling Kumang Branch Office Kelam, Kelam Permai District, Sintang Regency. This study uses a quantitative approach with multiple linear regression analysis. The sampling was conducted using a saturated sampling method, so that all 89 members of the population were included as respondents. The results of the study indicate that partially, interest rates do not have a significant effect on borrowers’ interest, with a significance value of 0.218 (> 0.05). This suggests that members’ decisions to apply for loans are not only influenced by the interest rate level, but also by non-financial factors such as trust and service convenience. Conversely, the loan collateral variable has a positive and significant effect on borrowers’ interest, with a significance value of 0.000 (< 0.05). The ease and flexibility of the collateral system are proven to increase members’ interest in borrowing. In addition, the F-test results show that interest rates and loan collateral together have a significant effect on borrowers’ interest, with a significance value of 0.000 (< 0.05). These findings emphasize the importance of credit policies that pay attention to the aspects of loan collateral to increase members’ participation in accessing loan services at CU Keling Kumang BO Kelam. Keywords: Credit Policy, Interest Rate, Loan Collateral, Borrowers' Interest.